2019
DOI: 10.1111/cas.14138
|View full text |Cite
|
Sign up to set email alerts
|

The competitive endogenous RNA regulatory network reveals potential prognostic biomarkers for overall survival in hepatocellular carcinoma

Abstract: The aim of the present study is to construct a competitive endogenous RNA (ceRNA) regulatory network by using differentially expressed long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in patients with hepatocellular carcinoma (HCC), and to construct a prognostic model for predicting overall survival (OS) of HCC patients. Differentially expressed lncRNAs, miRNAs, and mRNAs were explored between HCC tissues and normal liver tissues. A prognostic model was built for predicting OS of HCC patients and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…Indeed, phosphorylated SQSTM1/p62 has been shown to accumulate in the HCC tumor region, while its inhibitor may inhibit cell proliferation and resistance to anticancer agents [37]. Furthermore, multiple studies reported that SQSTM1 could serve as a novel prognostic biomarker in multiple cancers types, including nasopharyngeal carcinoma, lung cancer, oral squamous cell carcinoma, and HCC [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, phosphorylated SQSTM1/p62 has been shown to accumulate in the HCC tumor region, while its inhibitor may inhibit cell proliferation and resistance to anticancer agents [37]. Furthermore, multiple studies reported that SQSTM1 could serve as a novel prognostic biomarker in multiple cancers types, including nasopharyngeal carcinoma, lung cancer, oral squamous cell carcinoma, and HCC [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…(Evert et al 2013) In addition, H2AFX together with another seven genes, constitutes a prognostic signature for HCC with C-indexes of 0.776, 0.745, and 0.789 for 1-, 3-, and 5-year OS, respectively. (Zhang et al 2019b) EZH2 is important in determining the character of hepatic tumors and immunohistochemistry results showed that this protein was positively stained in various types of malignant liver tumors. However, EZH2 has not been detected in benign hepatic diseases, such as adenomas or cirrhotic nodules.…”
Section: Discussionmentioning
confidence: 99%
“…However, when we considered that all involved miRNAs and circRNAs should be significantly changed, there were only 26 miRNA-mRNA pairs and 71 circRNA-miRNA pairs remaining. Subsequently, a combination of 26 miRNA-mRNA pairs and 71 circRNA-miRNA pairs was used to construct a circRNA-miRNA-mRNA regulatory network, and was visualized using Cytoscape 3.4.0 (Figure 4), which contained 103 circRNA-miRNA-mRNA interactive groups (Table S2) and rat LR-associated circRNAs (48), miRNAs (20), and mRNAs (23).…”
Section: Circrna-mirna-mrna Regulatory Network Involved In Cell Prolimentioning
confidence: 99%
“…Recently, Bai et al [20] analyzed the regulatory role of the lncRNA-miRNA-mRNA network during the proliferative phase of rat liver regeneration. Moreover, accumulating evidence has revealed that the circRNA-miRNA-mRNA regulatory network has been demonstrated to be involved in gastric cancer [21], pancreatic ductal adenocarcinoma [22], hepatocellular carcinoma [23], etc/and more.…”
Section: Introductionmentioning
confidence: 99%